Pengetahuan Tentang Kesehatan Reproduksi terhadap Pemanfaatan Pusat Informasi dan Konseling Remaja (PIK-R) - Rino M; Tina Yuli Fatmawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Youth Information And Counseling Center (PIK-R) is one of the forums developed in the GenRe program, which is managed from Indonesia, which is the fourth country in the world that has the most population. The total population of Indonesia currently reaches 240 million people. Most of the population in Indonesia are teenagers. This study is a quantitative study, aims to determine the relationship between knowledge about reproductive health and the use of PIK-R among students at STIKES Baiturrahim. The research has been carried out in Mei-June 2021 at STIKes Baiturrahim. The sample was 108 people using the purposive sampling method. The study used the Chi-Square test. The results showed that knowledge was low as many as 55 people (50.9%), the use of PIK-R was not good as many as 49 people (45.4%) and the results of statistical bivariate obtained p-value = 0.343 < 0.05, it can be concluded that there is no significant relationship between Knowledge and the use of PIK-R for students at STIKES Baiturrahim. Students are advised to use PIK-R at STIKes Baiturrahim so that they can increase their knowledge, especially about adolescent reproductive health.